Genotypes of human metapneumovirus circulating during 2010‐2012 in children from Panama. Issue 3 (1st November 2017) - Ábrego, Leyda E.; Mirazo, Santiago; Delfraro, Adriana; Franco, Danilo; Castillo, Marlene; Gaitán, Melissa; Castillo, Juan; Moreno, Brechla; Pascale, Juan M.; Arbiza, Juan
Abstract : Human metapneumovirus (HMPV) is a common causative agent of severe respiratory tract infections in children under 5 years old, the elderly and immunocompromised patients, being responsible for 5‐15% of all viral respiratory infections requiring hospitalization. Though HMPV was included in the surveillance program for respiratory viruses in 2010, its genotype distribution remains unknown. Herein, 45 positive samples to HMPV from children ≤5 years old were characterized by phylogenetic analysis based on N gene sequence. Results showed the co‐circulation of four sub‐lineages: A2a (8.8%), A2b (55.5%), B1 (15.6%), and B2 (20%), demonstrating the genetic heterogeneity of HMPV circulating in Panamá.